Pemecahan Masalah Matematis Siswa SMP dalam Menyelesaikan Ill-Structured Problem Ditinjau dari Math Anxiety - Putri Dwi Juniyanti; Ika Kurniasari (Universitas Negeri Surabaya, 2026)
Mathematical problem solving is an important competency that students must possess to solve mathematical problems, especially ill-structured problems. However, emotional factors such as math anxiety can influence students’ problem solving processes. This study aims to describe the process of solving mathematical problems by junior high school students in solving ill-structured problems in terms of math anxiety. The study uses a qualitative approach with a descriptive research type. The subjects were eighth-grade junior high school students who had high and low math anxiety. Data were obtained from mathematics quiz, math anxiety questionnaire, ill-structured problem solving test, and interviews. The results showed that in the problem understanding stage, junior high school students with high math anxiety identified only partial information in the problem and did not plan their strategies in detail, consequently, during the strategy execution stage, they encountered obstacles and performed rechecks without basing them on the results of their solutions. Conversely, junior high school students with low math anxiety were able to identify information comprehensively, then relate it to prior knowledge and explain their solution strategy plans in detail so that they could carry out the steps according to plan, as well as review the solution steps in accordance with the context of the problem.